TINJAUAN MAQASID SYARIAH TERHADAP ISBAT NIKAH ANALISIS PENETAPAN HAKIM PENGADILAN AGAMA ARGA MAKMUR NOMOR 0110/PDT.P/2016/PA.AGM DAN NOMOR 0128/PDT.P/2016/PA.AGM - Armalina, Armalina (UIN Fatmawati Sukarno Bengkulu, 2018)
Maqasid Syariah is the objective of recommendation for Islamic law, while Isbat marriage is the endorsement of marriages that have been held according to Islamic Shari’a, but not recorded by Religious Affairs Office (KUA) or the Marriage Registry Official (PPN) authorized. The compilation of Islamic Law which has the power of Inpres limits the permissible cases to be attributed. The formulation of this research problem is how the basis of judges’ consideration as well as how the analysis of maqasidsyariah to the determination of the case Number 0110 / Pdt.P / 2016 / PA.AGM and Number 0128 / Pdt.P / 2016/ PA.AGM about isbat marriage. The research method was used qualitative descriptive analysis that was the data processing obtained in the field study result which then combined with data obtained from literature study, in order to obtainthe accurate data. The approach was used the juridical approach. The location of the research was conducted in Arga Makmur Religious Court. Primary data sources obtained through interviews with Judges involved in the establishment of isbat marriage. Second- ary data sources was included the legislation and court decisions, coupled with literature relevant to marriageisbat issues. The result of the research was found that judge consideration in the determination of case Number 0110 / Pdt.P / 2016 / PA.AGM and Number 0128 / Pdt.P / 2016 / PA.AGM on marriage isbat based on juridical, philosophical and sociological considerations. The juridical isbat marriage regulated in the Compilation of Islamic Law through Presidential Instruction Number 1 of 1991. The determination of marriage isbat was supported by the evidence on the facts in the hearing. Maqasid sharia in the case of marriage isbat in Islamic law that is to realize and maintain mashlahat mankind on marital status and status of child in marriage.. The stipulation of marriage isbat provides legal certainty to the legality of marriage both religionally and legally